Renal Operational Tolerance Is Associated With a Defect of Blood Tfh Cells That Exhibit Impaired B Cell Help. Issue 6 (19th January 2017) - Chenouard, A.; Chesneau, M.; Bui Nguyen, L.; Le Bot, S.; Cadoux, M.; Dugast, E.; Paul, C.; Malard‐Castagnet, S.; Ville, S.; Guérif, P.; Soulillou, J.‐P.; Degauque, N.; et al.
Abstract : Renal operationally tolerant patients (TOL) display a defect in B cell differentiation, with a deficiency in plasma cells. Recently described, T follicular helper (Tfh) cells play a critical role in B cell differentiation. We analyzed blood Tfh subsets in TOL and transplanted patients with stable graft function under immunosuppression (STA). We observed a reduced proportion of blood activated and highly functional Tfh subsets in TOL, without affecting Tfh absolute numbers. Functionally, Tfh cells from TOL displayed a modified gene expression profile, failed to produce interleukin‐21, and were unable to induce IgG production by naive B cells. This Tfh defect is linked to a low incidence of postgraft de novo donor‐specific antibody (dnDSA) immunization, suggesting that the lack of Tfh cells in TOL may induce a protolerogenic environment with reduced risk of developing dnDSA. Finally, we showed that elevated Tfh in STA precedes the occurrence of dnDSA during an alloresponse. These data provide new insights into the mechanisms of antibody response in operational tolerance. Disrupted homeostasis and impaired Tfh function in TOL could lead to a reduced risk of developing dnDSA and suggest a predictive role of blood Tfh cells on the occurrence of dnDSA in transplant recipients. Abstract : Renal operational tolerance is associated with a decreased percentage of blood CXCR5+ T follicular helper cells, including a highly functional CXCR3‐PD‐1+ subset that exhibits impaired B cell help with a lack of IL‐21 secretion.